2022
DOI: 10.2147/jir.s361541
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MIAT Regulates Hyperosmotic Stress-Induced Corneal Epithelial Cell Injury via Inhibiting the Caspase-1-Dependent Pyroptosis and Apoptosis in Dry Eye Disease

Abstract: Purpose The biological role and mechanism of long noncoding RNA (lncRNA) myocardial infarction-associated transcript (MIAT) in dry eye remain to be illustrated. Pyroptosis is a noticeable form of inflammatory activation, which is characteristic of gasdermin D (GSDMD)-driven cell death. The present study was designed to explore the role of MIAT in pyroptosis and apoptosis induced by hyperosmolarity stress (HS) in human corneal epithelial cells (HCECs). Methods HCECs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…There were many researches demonstrated that IL-1β was up-regulated in DED patients [9,27,28]. In addition to pyroptosis, caspase-1 is also involved in apoptosis in inflammatory situations [29]. Our results showed that IL-1β was highly expressed in DED model hCECs, and IL-1β silencing inhibited the thermal degeneration of DED model hCECs (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…There were many researches demonstrated that IL-1β was up-regulated in DED patients [9,27,28]. In addition to pyroptosis, caspase-1 is also involved in apoptosis in inflammatory situations [29]. Our results showed that IL-1β was highly expressed in DED model hCECs, and IL-1β silencing inhibited the thermal degeneration of DED model hCECs (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…This, in turn, hampers the process of wound healing in traumatized ocular tissues. 18 , 19 Prior investigations into the interplay between DRD1 and inflammation have revealed that DRD1 functions as an anti-inflammatory agent by impeding activation of the NLRP3 inflammasome and the subsequent release of inflammatory cytokines, including caspase-1 and IL-1β. 6 Recent studies have elucidated the anti-inflammatory effects of DRD1 in conditions such as cerebral hemorrhage, acute kidney injury, and cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a new mechanism for dexamethasone as an anti-inflammatory drug in dry eye. Long noncoding RNAMIAT has also been reported to regulate corneal epithelial cell damage induced by hyperosmotic stress by inhibiting Caspase-1-dependent corneal epithelial cell pyroptosis [24].…”
Section: Pyroptosis and Dry Eyementioning
confidence: 99%